Energy transition metals - Lukas Boer; Andrea Pescatori; Martin Stuermer (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
The energy transition requires substantial amounts of metals such as copper, nickel, cobalt and lithium. Are these metals a key bottleneck? We identify metal-specific demand shocks, estimate supply elasticities and pin down the price impact of the energy transition in a structural scenario analysis. Metal prices would reach historical peaks for an unprecedented, sustained period in a net-zero emissions scenario. The total value of metals production would rise more than four-fold for the period 2021 to 2040, rivaling the total value of crude oil production. Metals are a potentially important input into integrated assessments models of climate change.
Keywords: C32; C53; Q3; Q4; Q54; 330; Conditional forecasts; structural vector autoregression; structural scenario analysis; energy transition; metals; fossil fuels; prices; climate change